Civil Society and Government (Princeton, 2002)
Civil Society and Government brings together an unprecedented array of political, ethical, and religious perspectives to shed light on the complex and much-debated relationship between civil society and the state. Some argue that civil society is a bulwark against government; others see it as an indispensable support for government. Civil society has been portrayed both as a independent of the state and as dependent upon it. This book reveals the extraordinary diversity of views on the subject by examining how civil society has been treated in classical liberalism, liberal egalitarianism, critical theory, feminism, natural law, Christianity, Judaism, Islam, and Confucianism.